Parotid Gland Biopsy as an Additional Diagnostic Tool for Supporting the Diagnosis of Sjögren's Syndrome. (14th July 2011) - Soyfoo, Muhammad S.; Catteau, Xavier; Delporte, Christine
Abstract : Sjögren's syndrome (SS) is an autoimmune disease characterized by keratoconjunctivitis sicca and xerostomia. There are actually no diagnostic criteria for SS, but classification criteria based on the revised American-European criteria have been elaborated. These include subjective criteria: ocular and oral symptoms, and objective criteria: ocular, histopathological, oral, and serological signs. SS is considered if 4 of the 6 criteria are present, when histopathology or serology is positive, or if 3 of any 4 objective criteria are present. A patient presented with both ocular and oral symptoms and signs but did not meet the SS classification criteria. Indeed, no anti-SSA or anti-SSB antibodies were detected, and minor salivary gland biopsy was normal. To further understand the origin of the sicca symptoms, a parotid gland biopsy was performed and showed important lymphocytic infiltrates. This could account for the sicca symptoms and signs since parotid glands are one the major contributors to salivary flow. Therefore, parotid gland biopsy could be a useful asset for the diagnosis of SS.